2021
DOI: 10.3390/ijms22168384
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Inactivation of an Endodontic Bacteria Using Diode Laser and Indocyanine Green-Loaded Nanosphere

Abstract: Apical periodontitis, an inflammatory lesion causing bone resorption around the apex of teeth, is treated by eradicating infectious bacteria from the root canal. However, it has a high recurrence rate and often requires retreatment. We investigated the bactericidal effect of antimicrobial photodynamic therapy (aPDT)/photodynamic antimicrobial chemotherapy (PACT) using indocyanine green (ICG)-loaded nanospheres coated with chitosan and a diode laser on a biofilm of Enterococcus faecalis, a pathogen of refractor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 53 publications
1
4
0
1
Order By: Relevance
“…Stronger antibacterial activity was received when ICGloaded nanospheres coated with chitosan were applied. Irradiation of the root surface at 2.1 W for 5 min resulted in a reduction of E. faecalis by 1.89 log, which was similar to the findings of the present study (ICG 500 and 1000 µg/mL) [50]. Other authors observed sufficient antibacterial effects when ICG was conjugated to nano-curcumin and metformin or by applying more sufficient laser settings [29,51].…”
Section: Discussionsupporting
confidence: 91%
“…Stronger antibacterial activity was received when ICGloaded nanospheres coated with chitosan were applied. Irradiation of the root surface at 2.1 W for 5 min resulted in a reduction of E. faecalis by 1.89 log, which was similar to the findings of the present study (ICG 500 and 1000 µg/mL) [50]. Other authors observed sufficient antibacterial effects when ICG was conjugated to nano-curcumin and metformin or by applying more sufficient laser settings [29,51].…”
Section: Discussionsupporting
confidence: 91%
“…Microbiological sampling techniques to detect bacterial presence have also been proposed as an alternative means to decide when shaping and cleaning procedures in vivo are completed, suggesting when they can obturate properly disinfected canals. However, these microbial culturing techniques that quantify bacterial presence (and not residual debris) are not simple to use in a clinical environment, and are currently used mostly for in vitro studies [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, these microbial culturing techniques that quantify bacterial presence (and not residual debris) are not simple to use in a clinical environment and are currently used mostly for in vitro studies [11][12][13].…”
Section: Introductionmentioning
confidence: 99%